Under the Umbrella of Custom: Harmonious Relationship between Christian and Islam in Tiga Beringin Village and Simpang Pergendangan Village, Karo - Ginting, Junita Setiana; Sumarno, Edi; Karina, Nina; Handoko, Handoko (Budapest International Research and Critics University, 2020)
Indonesian society is a pluralistic society. The pluralism of society can be seen from the diversity of languages, ethnicities and religions. This pluralism is also reflected in the diverse Karo community in embracing religions such as Christian, Catholic, Islam and ancestral religions. Many religions are believed by Karo community, but the community's stigma still places that Karo community are Protestant Christians. Behind this stigma, there is a community of society whose entire population is Muslim. The villages are Tiga Beringin Village and Simpang Pergendangan Village, Tiga Binanga Sub-district. However, how is the relationship between the community groups well established and why there has never been a problem by the majority Christian population? This article will answer the things mentioned above which tell how the relationship between the community is harmoniously established and conflicts never occur.